Institutional Climate and Barriers for Intensive Innovation - A. A. Nikonova (Управление)
The issues, concerning institutional climate conducive to the creation and diffusion of innovation, are discussed in the article. Comparative analysis of institution identifies significant gaps in institutional climate in different countries. Two groups of requirements have been identified in order to improve the quality of institutional environment for Russian innovators. The basic requirements are due to the patterns of scientific and technical development of the global economy; as a rule, they are common for all countries. The special requirements are determined by the spatial, sectoral and other internal factors. We distinguish requirements for institution in countries with developed industry and less developed one. We show that it is important to focus on the development and diversity of channels for transfer of knowledge and technology in such country as Russia. The shift in innovation paradigm focuses on the efforts to improve communicative character of institutional climate and to create innovation ecosystems.